Evaluating the Effectiveness of Mental Health First Aid Program for Chinese People in Hong Kong. (January 2017) - Wong, Daniel F. K.; Lau, Ying; Kwok, Sylvia; Wong, Prudence; Tori, Christopher
Purpose: Chinese people generally lack knowledge of mental illness. Such phenomenon may lead to a delay in seeking psychiatric treatments. This study evaluated the effectiveness of Mental Health First Aid (MHFA) program in improving mental health knowledge of the general public in Hong Kong. Methods: A quasi-experimental design was adopted whereby 138 participants received MHFA training and 139 partook in seminars on general health, respectively. All participants filled out a standardized questionnaire before, at the end, and 6-month after the training. Results: Findings demonstrated that MHFA training might be effective in enhancing participants' knowledge of mental disorders, reducing stigma, and improving perceived confidence in providing help to people with mental illness. Effect size statistics revealed mostly modest to moderate improvements in major variables in the experimental group. Conclusion: It is recommended that culturally attuned MHFA program can be used as prevention strategy to promote good mental health in Chinese communities.